Gamma Knife Radiosurgery for Acromegaly - John D. Rolston; Lewis S. Blevins (International Journal of Endocrinology)
Acromegaly is debilitating disease occasionally refractory to surgical and medical treatment. Stereotactic radiosurgery, and in particular Gamma Knife surgery (GKS), has proven to be an effective noninvasive adjunct to traditional treatments, leading to disease remission in a substantial proportion of patients. Such remission holds the promise of eliminating the need for expensive medications, along with side effects, as well as sparing patients the damaging sequelae of uncontrolled acromegaly. Numerous studies of radiosurgical treatments for acromegaly have been carried out. These illustrate an overall remission rate over 40%. Morbidity from radiosurgery is infrequent but can include cranial nerve palsies and hypopituitarism. Overall, stereotactic radiosurgery is a promising therapy for patients with acromegaly and deserves further study to refine its role in the treatment of affected patients.